ANALISIS POTENSI INTERAKSI OBAT ANTIDIABETIK ORAL PADA PASIEN DI INSTALASI RAWAT JALAN ASKES RUMAH SAKIT DOKTER SOEDARSO PONTIANAK PERIODE JANUARI- MARET 2013 - ., Mega Gustiani Utami (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Drug interaction is one of eight drug-related problems categories that may affectpatient clinical outcome. Increasing complexity of the drugs used in current treatment andthe likelihood of polypharmacy practices, make possible the incident of drug interactions.The research aims to know the number and mechanism of the drug-drug interactions inprescriptions contains oral antidibetic, identify drugs are often interact as well as analyzecorrelation between the number of medication in one prescription with drug interactionfound. The study was conducted in dr. Soedarso hospital, Pontianak from the January toMarch 2013. The research used non-experimental methodology by using descriptiveanalysis in a retrospective way. Data analysis using Chi-Square Test on SPSS 17.0. From1435 outpatient prescription sheets that meet the inclusion criteria, found that druginteractions occur 62.16% prescription which received medication oral antidibetic. Thepatterns of interaction mechanism are pharmacokinetic interaction 13.56%,pharmacodynamics 34.15%, and unknown 52.29%. The types of drugs that often interact,among metformin and gliclazide. Incidence of drug interactions occur 6 times higher insubjects who received ? 5 drugs compared with patients who received < 5. The result ofstatistical analysis showed that there is significant correlation between the number ofmedication in one prescription with incidence of drug interaction found drugs (p<0.05).Keyword : drug inteaction, oral antidiabetic, dr. Soedarso hospital